Impact of parental boundary ambiguity on children’s adjustment to divorce - Guyette, Erin Jane (Kansas State University, 2020)
Due to the large number of children who experience parental divorce, researchers have focused on the impact of divorce on children and protective factors to reduce negative consequences. Divorce requires a re-negotiation of relational boundaries to be forced to be negotiated due to the change in the family system and transition from parents being romantic partners to coparents. Using data from 739 divorced mothers and fathers with a child between the ages of 4 and 18, I examined the influence of coparental boundary ambiguity and time since separation on three child well-being factors: prosocial skills, externalizing behaviors, and internalizing behaviors. Boundary ambiguity between coparents was found to negatively affect children’s prosocial skills and externalizing and internalizing behaviors. Boundary ambiguity was found to decrease over time; however, time was not significant as a moderator between boundary ambiguity and child well-being factors (externalizing behaviors, internalizing behaviors, and prosocial skills). Mental health professionals and other practitioners working with divorcing families can use these findings to prompt discussions between coparents about establishing child-focused boundaries.
Keywords: Divorce; Separation; Child well-being; Boundary ambiguity